POLA MAKAN TERHADAP KEJADIAN HIPERTENSI - Angelina, Yulia; Astuti Purnamawati, Ditha; Pradika, Jaka (Literasi Intelektual, 2024)
Background: Hypertension is a condition where systolic pressure is ≥140 mmHg and diastolic pressure is ≥90 mmHg. Uncontrolled hypertension can lead to complications such as heart attack, coronary heart disease, heart failure, and stroke. One way to control blood pressure is by maintaining a healthy diet. Objective: To determine the effect of dietary patterns on the incidence of hypertension among the elderly in the Pal 3 Pontianak Health Center working area. Methods: This quantitative study used a cross-sectional design to analyze the relationship between diet and hypertension. A total of 138 elderly respondents were selected using accidental sampling. Data were collected through questionnaires and observations, then analyzed descriptively and analytically. Results: Most respondents had poor dietary patterns (92 or 67%), and the majority experienced grade I hypertension (85 or 62%). The combination of poor diet and grade I hypertension was found in 55 respondents (65%). The Spearman-rho test showed a significant relationship (p = 0.01) between diet and the incidence of hypertension. Conclusion: Dietary patterns significantly influence hypertension among the elderly in the Pal 3 Pontianak Health Center area. Health workers are encouraged to educate the elderly about proper nutrition and healthy eating habits to prevent and control hypertension